Pendidikan dalam Keluarga Berbasis Etika Buddha - Sapardi, Sapardi (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
This study aims to find out familial education on the basis of Buddhist ethics and the relationship of Buddhist teachings in building a happy, prosperous family life. The foregoing rests upon the identification of texts from the Tipitaka / Tripitaka Scriptures related to Education in the Family and moral ethics (Sila), and the texts are subsequently analyzed and dissected using the theory of structural functionalism and hermeneutics. Based on the analysis of the aforesaid text data, it can be seen the role of moral ethics that must be put forward and become a guide in shaping a happy and prosperous family life. Education in the Family is a pattern or method that must be done by a Buddhist household. Based on ethics in managing hittasukkhaya life, it becomes the basis and guide in creating happy and prosperous home life (hitta sukkhaya). Moral ethics (Sila) is the basis and foundation and guide for householders in creating a happy and prosperous life in the face of various changes that occur in the current modern era.